Shear bond strength of resin composite bonded with two adhesives: Influence of Er: YAG laser irradiation distance - Shirani, Farzaneh (Dent Res J (Isfahan), 2014)
BACKGROUND: Dental surfaces prepared with different Er:YAG laser distance may have different characteristics compared with those prepared with conventional instruments. The aim of this study was to investigate the effect of Er:YAG laser irradiation distance from enamel and dentin surfaces on the shear bond strength of composite with self-etch and etch and rinse bonding systems compared with conventional preparation method. MATERIALS AND METHODS: Two hundred caries-free human third molars were randomly divided into twenty groups (n = 10). Ten groups were designated for enamel surface (E1-E10) and ten for dentin surface (D1-D10). Er: YAG laser (2940 nm) was used on the E1-E8 (240 mJ, 25 Hz) and D1-D8 (140 mJ, 30 Hz) groups at four different distances of 0.5 (standard), 2, 4 and 11 mm. Control groups (E9, E10, D9 and D10) were ground with medium grit diamond bur. The enamel and dentin specimens were divided into two subgroups that were bonded with either Single Bond or Clearfil SE Bond. Resin composite (Z100) was dispensed on prepared dentin and enamel. The shear bond strengths were tested using a universal testing machine. Data were analyzed by SPSS12 statistical software using three way analysis of variance, Tukey and independent t-test. P < 0.05 was considered as significant. RESULTS: There was a significant difference between enamel and dentin substrates (P < 0.001) and between lased and un-lased groups; the un-lased group had significantly higher bond strength (P < 0.001). Shear bond strength increased significantly with an increase in the laser irradiation distance (P < 0.05) on enamel surfaces (in both bonding agent subgroups) and on dentin surfaces (in the Single Bond subgroup). CONCLUSION: Laser irradiation decreases shear bond strength. Irradiation distance affects shear bond strength and increasing the distance would decrease the negative effects of laser irradiation.